An investigation of surface deformations occurring at the contact edges of statically loaded discs - Jones, D. A.; Reason, B. R. (College of Aeronautics, 1964)
An investigation has been carried out, using statically loaded steel and 'Perspex' discs, into elastic displacements occurring at the axial extremities of the Hertzian flat. By employing the technique of 'Photostress', together with optical magnification, it has been found possible to inspect in detail the disposition of strain around these points. Using a 'step grinding' technique a qualitative three-dimensional envelope of surface displacements has been constructed. The effect of these displacements is considered in relation to 'edge pitting' of discs.